Fast comprehensive single‐sequence four‐dimensional pediatric knee MRI with T2 shuffling. Issue 6 (11th October 2016) - Bao, Shanshan; Tamir, Jonathan I.; Young, Jeffrey L.; Tariq, Umar; Uecker, Martin; Lai, Peng; Chen, Weitian; Lustig, Michael; Vasanawala, Shreyas S.
Abstract : Purpose: To develop and clinically evaluate a pediatric knee magnetic resonance imaging (MRI) technique based on volumetric fast spin‐echo (3DFSE) and compare its diagnostic performance, image quality, and imaging time to that of a conventional 2D protocol. Materials and Methods: A 3DFSE sequence was modified and combined with a compressed sensing‐based reconstruction resolving multiple image contrasts, a technique termed T 2 Shuffling ( T 2 Sh). With Institutional Review Board (IRB) approval, 28 consecutive children referred for 3T knee MRI prospectively underwent a standard clinical knee protocol followed by T 2 Sh. T 2 Sh performance was assessed by two readers blinded to diagnostic reports. Interpretive discrepancies were resolved by medical record chart review and consensus between the readers and an orthopedic surgeon. Image quality was evaluated by rating anatomic delineation, with 95% confidence interval. A Wilcoxon rank‐sum test assessed the null hypothesis that T 2 Sh structure delineation compared to conventional 2D is unchanged. Intraclass correlation coefficients were calculated for interobserver agreement. Imaging time of the conventional protocol and T 2 Sh was compared. Results: There was 81% and 87% concordance between T 2 Sh reports and diagnostic reports, respectively, for each reader. Upon consensus review, T 2 Sh had 93% sensitivity and 100% specificity compared to clinical reports for detection of clinically relevant findings. The 95% confidence interval of diagnostic or better rating was 95–100%, with 34–80% interobserver agreement. There was no significant difference in structure delineation between T 2 Sh and 2D, except for the retinaculum ( P < 0.05), where 2D was preferred. Typical imaging time for T 2 Sh and the conventional exam was 7 and 13 minutes, respectively. Conclusion: A single‐sequence pediatric knee exam is feasible with T 2 Sh, providing multiplanar, reformattable 4D images. Level of Evidence : 2 J. MAGN. RESON. IMAGING 2017;45:1700–1711